A spacer fabric-based three-dimensional patterning method with two-colored jacquard systems. Issue 11 (June 2021) - Li, Xinxin; Tian, Meiling; Liu, Yanping; Li, Ya
To generate three-dimensional (3D) patterned spacer structures with non-continuous jacquard appearance in two colors, such as the yarn-cutting style, this paper attempts to propose a novel 3D patterning method based on the single jacquard technique. Two sets of jacquard threads are spaced apart and threaded in split bars as two patterning systems with separate colors. Then, for independent patterns, each single loop should be able to be selectively observable on patterned layers and hidden in the spacer layer. Cases of continuous jacquard loops and zero-loop ones in both course and wale directions are to be solved based on the characteristic of one-wale left offset. Besides, by differing the moment when offset occurs, jacquard threads are transferred from stitching on both layers to a single or zero layer, thus enabling one to hide jacquard loops in non-patterning areas. This approach theoretically brings new patterning possibilities to 3D spacer structures with the single jacquard technique.